Measuring health inequity amongst a cohort of HIV positive mother and child pairs in South Africa : the relationship between household socio-economic status and child health outcomes - Nkonki, Lungiswa Leonora (Health Economics Unit, 2014)
Includes bibliographical references (leaves 105-122).